2017
DOI: 10.1182/blood-2017-03-773341
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the osteocyte-specific protein sclerostin increases bone mass and fracture resistance in multiple myeloma

Abstract: Multiple myeloma (MM) is a plasma cell cancer that develops in the skeleton causing profound bone destruction and fractures. The bone disease is mediated by increased osteoclastic bone resorption and suppressed bone formation. Bisphosphonates used for treatment inhibit bone resorption and prevent bone loss but fail to influence bone formation and do not replace lost bone, so patients continue to fracture. Stimulating bone formation to increase bone mass and fracture resistance is a priority; however, targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(176 citation statements)
references
References 59 publications
9
167
0
Order By: Relevance
“…SOST is a vital negative regulator of bone formation. It has recently been reported that SOST inhibition increases bone formation in several disorders . Delgado‐Calle et al have shown that SOST inhibition augmented osteoblast numbers, promoted new bone formation and decreased osteoclast number in multiple myeloma‐colonized bone .…”
Section: Discussionmentioning
confidence: 99%
“…SOST is a vital negative regulator of bone formation. It has recently been reported that SOST inhibition increases bone formation in several disorders . Delgado‐Calle et al have shown that SOST inhibition augmented osteoblast numbers, promoted new bone formation and decreased osteoclast number in multiple myeloma‐colonized bone .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, there were no significant differences in sclerostin expression by osteocytes in MM patients when compared with healthy controls, suggesting that higher sclerostin levels could be secreted directly by myeloma cells rather than by osteocytes (Giuliani et al, 2012). The inhibition the osteocyteproduced sclerostin led to an increase in the bone mass, to prevention of bone destruction and to fracture resistance in mice myeloma models (Delgado-Calle et al, 2017;McDonald et al, 2017). The inhibition the osteocyteproduced sclerostin led to an increase in the bone mass, to prevention of bone destruction and to fracture resistance in mice myeloma models (Delgado-Calle et al, 2017;McDonald et al, 2017).…”
Section: The Central Role Of Osteocytesmentioning
confidence: 99%
“…More recently, deletion of the sclerostin gene ( Sost ) or administration of an anti‐sclerostin antibody prevented bone disease in murine models of myeloma . Furthermore, when an anti‐sclerostin treatment was used in combination with Zol in preclinical models of myeloma, using a preventative regimen, they showed superior effects on fracture resistance compared with Zol alone . However, sclerostin's effectiveness on established osteolytic bone disease has not yet been assessed in murine models or in patients with myeloma.…”
Section: Introductionmentioning
confidence: 99%